A comprehensive comparative study of CdTe thin films grown on ultra-thin glass substrates by close-spaced sublimation and RF magnetron sputtering - Doroody C.; Rahman K.S.; Rosly H.N.; Harif M.N.; Sopian K.; Abdullah S.F.; Amin N. (Elsevier B.V., 2023)
Cadmium telluride; Crystallite size; II-VI semiconductors; Magnetron sputtering; Scanning electron microscopy; Sublimation; Substrates; Thin films; Cadmium telluride thin films; Close spaced sublimation; Comparatives studies; R.F. magnetron sputtering; RF sputtering; Sputtered films; Structural characteristics; Thin glass substrates; Ultra-thin; Ultra-thin glass; Glass